Model development and analysis of radar backscatter in Ross Island, Antarctica - Albert, M. D.; Chuah, H. T.; Ewe, H. T.; Syahali, Syabeela (IEEE Xplore, 2005)
Antarctica remains the continent with least access to humans due to its harsh weather condition and remoteness from human civilization. However, the major heat sink effect and its critical role in balancing world climate have made Antarctica an important continent to monitor and understand constantly. Due to its remoteness and wide area coverage, remote sensing technology is suitable to be utilized for such purposes. As the majority parts of Antarctia are covered by ice and snow, it is necessary to model the ice and snow media for microwave scattering analysis to interpret from the data. In this paper, a theorethical model is developed to model the sea ice and ice shelf areas in Antarctica by treating them as layers of random discrete medium with scatterers embedded in the host medium. The Dense Medium Phase and Amplitude Correction Theory (DMPACT) which takes into account the close spacing effect among the scatterers is applied to the sea and snow medium [1]. The air-snow interface and snow-sea interface are modelled using Integral Equation Method (IEM) with the consideration of surface multiple scattering effect [2]. This scattering problem of an electrically dense medium such as sea ice and ise shelf is solved using the Radiative Transfer Theory. Gound truth measurement trips were conducted in the years of 2002-2004 at Ross Island, Antarctica with logistic assistance of Antarctica New Zealand to measure the physical parameters of the sea ice, ice shelf and sea water, which were then used in theorethical model calculation. RadarSat images of the study sites were also acquired for the comparison with the theorethical results. The results indicate that the matches between the theorethical predictions and the satellite data over the measurement period are promising. In the theorethical analysis, a study of the physical paraneters affecting the backscattering returns and the major scattering mechanisms involveds is carried out and the analysis is presented.